Negotiating gender scripts in mobile dating apps: between affordances, usage norms and practices. Issue 8 (11th June 2021) - Comunello, Francesca; Parisi, Lorenza; Ieracitano, Francesca
ABSTRACT: The paper explores the perception and negotiation of gender representations and scripts among Italian dating app users. Adopting a gender perspective and a socio-technical framework, it describes how dating app affordances support the performance of gender scripts and explores how users negotiate gender scripts. We conducted 8 focus groups involving 39 dating app users from a variety of gender and sexual orientations. The results show how shared usage norms and practices disclose dominant gender scripts at play, and illustrate how some users try to subvert them. Participants are aware of a number of traditional and stereotypical gender scripts and broadly adhere to them; nevertheless, such scripts are partially reframed in the context of dating apps. Dating apps are mainly understood in terms of affordances, when participants highlight the ways in which they or their mates reduce the incidence of traditional scripts. On the other hand, dating apps' constraints emerge when some users try to detach themselves from common scripts, or when they struggle to perform traditional scripts in a context they perceive as inadequate. Results highlight how dating app users negotiate gender scripts: affordances and constraints of dating apps shape user practices and influence the performance and 'de-inscription' of gender scripts, without directly fostering the adoption of alternative scripts.